Probing the tau electric dipole moment at the BEPC-II collider - Bernreuther, Werner; Chen, Long; Nachtmann, Otto (Physical review, 2021)
We investigate the prospects of the search for a nonzero τ EDM form factor dτ(s) in τ-pair production by e+e− collisions at BEPC-II collider energies. We compute the expectation values and covariances of simple and optimal CP-odd observables for τ-pair production at √s=4.18 and 4.95 GeV with subsequent decays of τ± into major leptonic or semihadronic modes. For the τ decays to two pions and three charged pions, we take the full kinematic information of the hadronic system into account. Applying cuts and using realistic assumptions on the eventually attainable integrated luminosities at these energies, L(4.18)=3×104 pb−1 and L(4.95)=104 pb−1, respectively, we find the following. By taking into account purely semihadronic and semihadronic-leptonic τ+τ− decays one can achieve with optimal CP-odd observables the 1 s.d. sensitivities δRedτ=4.5×10−18 e cm (5.3×10−18 e cm) and δImdτ=2.2×10−18 e cm (2.7×10−18 e cm) at √s=4.18 GeV (4.95 GeV).
Gesehen am 15.02.2022